Sales well-being: a salesperson-focused framework for individual, organizational, and societal well-being. Issue 1 (2nd January 2023) - Dugan, Riley; Ubal, Valentina Ortiz; Scott, Maura L.
Abstract: Although the topic of well-being has become an increasingly prominent topic of discussion amongst scholars and practitioners alike, it has heretofore been given scant attention in the academic sales discipline. The current research attempts to correct this notable omission by developing a vision of salesforce well-being as it pertains to the people, processes, and performance metrics associated with the sales function. We posit that the concept of well-being is of enduring importance to the many stakeholders impacted by professional sales organizations. We conclude our research by offering a series of research questions for interested scholars who, in lending insight into these questions, will advance both academic theory and provide needed insights to sales organizations who must increasingly attend to the well-being of their employees, customers, suppliers, and communities.